Deer antler stem cells are a novel type of cells that sustain full regeneration of a mammalian organ—deer antler - Wang, Datao (Cell Death Dis, 2019)
Deer antlers are extraordinary mammalian organs that can fully regenerate annually. Antler renewal is a stem cell-based epimorphic process and antler stem (AS) cells can initiate de novo generation of antlers in postnatal mammals. However, although being called stem cells, the AS cells have not been characterized at molecular level based on the stem cell criteria. Comprehensive characterization of the AS cells would undoubtedly help to decipher the mechanism underlying the full regeneration of deer antlers, the only case of stem cell-based epimorphic regeneration in mammals. In the present study, three types of AS cells (antlerogenic periosteal cells APCs, for initial pedicle and first antler formation; pedicle periosteal cells PPC, for annual antler regeneration; and reserve mesenchyme cells RMCs, for rapid antler growth), were isolated for comprehensive molecular characterization. A horn-growth-related gene, RXFP2, was found to be expressed only in AS cells lineages but not in the facial periosteal cells (FPCs, locates geographically in the vicinity of the APCs or PPCs), suggesting the RXFP2 might be a specific marker for the AS cell lineage in deer. Our results demonstrated that AS cells expressed classic MSC markers including surface markers CD73, CD90, CD105 and Stro-1. They also expressed some of the markers including Tert, Nestin, S100A4, nucleostemin and C-Myc, suggesting that they have some attributes of the ESCs. Microinjection of male APC into deer blastocysts resulted in one female foetus (110 days gestation) recovered with obvious pedicle primordia with both male and female genotype detected in the ovary. In conclusion, the AS cells should be defined as MSCs but with partial attributes of ESCs.